High dietary non-starch polysaccharides detrimental to nutrient digestibility, digestive enzyme activity, growth performance, and intestinal morphology in largemouth bass, Micropterus salmoides - Liu, Yu; Fan, Jiongting; Huang, Huajing; Zhou, Hang; Cao, Yixiong; Zhang, Yumeng; Jiang, Wen; Zhang, Wei; Deng, Junming; Tan, Beiping (Frontiers in Nutrition, 2022)
An 8-weeks feeding trial was carried out to evaluate the effects of different levels of dietary non-starch polysaccharide on the growth, apparent nutrient digestibility, intestinal development, and morphology of largemouth bass (Micropterus salmoides). Seven isoproteic and isolipidic experimental diets were formulated (crude protein 47.00%, crude lipid 12.50%), containing 0, 3, 6, 9, 12, 15, and 18% non-starch polysaccharides (NSPs) (named Control, NSPs3, NSPs6, NSPs9, NSPs12, NSPs15, and NSPs18), respectively. Dietary inclusion of NSPs below 9% showed no negative impacts on fish growth and feed utilization efficiency, whereas dietary NSPs inclusion level above 9% decreased weight gain rate, specific growth rate, protein efficiency, protein deposition rate, apparent digestibility of dry matter and protein, and were accompanied by a reduction in intestinal protease, Na+/K+-ATPase and alkaline phosphatase activity and an increase in feed intake and feed coefficient. The activity of lipase was significantly decreased when dietary inclusion of 15 and 18% NSPs. Moreover, the lipid deposition rate and the apparent digestibility of lipids were significantly decreased since dietary inclusion of 9% NSPs. Dietary inclusion of NSPs above 12% significantly up-regulated intestinal GLP-2 gene’s expression, and was accompanied by significant changes in hindgut morphology, including increases in villus length and width, muscularis thickness and number of goblet cell, as well as a decrease in crypt depth. Additionally, dietary inclusion of NSPs above 3% significantly increased intestinal length index, and the viserosomatic index was significantly increased when dietary NSPs exceeded 15%. The linear regression analysis based on weight gain rate and feed coefficient showed that the appropriate dietary NSPs level of juvenile largemouth bass should not above 5.51%. In conclusion, high dietary NSPs adversely affects digestive enzyme activity and intestinal morphology, which in turn reduced the apparent digestibility of dietary nutrients and growth of juvenile largemouth bass.